Queering Serbian Archaeology: Androcentrism, Heteronormativity, Gender and the Writing of (Pre)history - Matić, Uroš (Ex Novo: Journal of Archaeology, 2024)
In scholarly backroom discussions, archaeologies of the Balkans are often labelled as conservative and ignorant of gender studies, their impact on archaeology, and how it deals with gender in the past. Indeed, androcentrism and heteronormativity are commonly found in archaeological interpretations throughout the Balkans, but not there alone. In this paper I will analyse how gender and sexuality in the past have been approached by some archaeologists in Serbia, a west-central Balkan country, and argue that, although some positive changes can be detected more critical gender and queer archaeologies are direly needed for two reasons. First and foremost, theoretically informed approaches to gender, in contrast to approaches based on gender stereotypes and heteronormativity, can lead to better thought-through and more informed reconstructions of the past. I illustrate this with several examples from mortuary and settlement archaeology. Secondly, and no less importantly, self-reflexive and theoretically informed approaches to gender and sexuality should have an activist component, helping to build a more just and democratic society. Therefore, we are never really done with gender archaeology. The latter is particularly needed in the Balkans, including Serbia, where there is an ongoing struggle against patriarchal ideologies and homophobia. In this respect, a dialogue is needed between archaeologists and the marginalized and oppressed communities and organisations fighting for basic human rights in the region.